Mobility of top income taxpayers in response to regional differences in personal taxes: Evidence from Spain - Julio López Laborda; Fernando Rodrigo Sauco (Economics: The Open-Access, Open-Assessment Journal, 2022)
The study empirically tests whether regional differences in personal taxes (Personal Income Tax, Wealth Tax, and Inheritance and Gift tax) have had some influence on the decision of the richest Spanish taxpayers to change their residence. The estimates use the Personal Income Tax (IRPF) Panel database provided by the Ministry of Public Finance. The study offers evidence that regional tax differences affect the decision to change residence of the top income taxpayers and also that this decision is also affected by other attractiveness and opportunity factors offered by the regions, and by certain characteristics of the individuals. However, the marginal effects are very slight, except for the coefficient of the variable showing regional differences in IRPF: If the difference between average regional IRPF rates increases by 10 percentage points in favour of the other regions, the probability of a top 1% taxpayer changing its residence increases by 11.2 percentage points. The study also documents the importance of the Community of Madrid in the relocation decisions of rich taxpayers. Finally, the study finds that the behaviour of taxpayers aged 65 years and over in the top 1% does not seem very different from that of all taxpayers in the same income bracket.
Keywords: 330; migration; personal income; regions; top income; wealth taxes